Papyri.info (Institute for the Study of the Ancient World, 2006)
[Dt.:] Die Datenbank erfaßt Texte in griechischer und lateinischer Sprache, die den nicht-literarischen Papyri der ptolemäischen und römischen Zeit entstammen. Die Texte lassen sich nach verschiedenen Kriterien durchsuchen. - [Engl.:] The database covers texts in greek and latin language, which are originated from the non-literary papyri of the Ptolemaic and Roman period. The whole texts can be searched by different criteria.
Gesehen am 10.06.14
Keywords: Website; Latein; Griechisch; Ägypten; Papyrus